Evaluating the accessibility of public service facilities to tourists and residents in island destinations: Evidence from the Changhai County - Xiaoling Zheng; Xiaoling Zheng; Dong Zhao (Frontiers Media S.A., 2023)
With the increasing diversity of social groups, public service facilities need to meet the diverse needs of different groups. However, there is still a lack of in-depth research evaluating urban public service facilities for diverse groups. Therefore, this paper use Kernel density spatial analysis method to delimits the research area based on data on the temporal and spatial behavior of islanders and tourists, and use urban network analysis (UNA) method to evaluates the public service facilities of the spatially overlapping area from the aspects of facility accessibility and availability. The study shows that (1) the spatial dislocation between facilities and residential places is serious, which leads to redundant construction or a lack of configuration of facilities in some areas. (2) The public service facilities in some areas can be used by tourists and residents to a similar degree, the number of facilities accessible to residents and tourists within a certain distance is not much different, and the configuration of facilities is relatively reasonable. (3) The overall configuration of infrastructure is biased toward residents, but the configuration of facilities in some areas can also reflect group fairness. The results indicate that the public facilities have a tendency to serve residents, and the results can give some suggestions for public facilities configuration to build a human-oriented island.